Pregnancy After Breast Cancer: A Systematic Review and Meta-Analysis. Issue 29 (10th October 2021) - Lambertini, Matteo; Blondeaux, Eva; Bruzzone, Marco; Perachino, Marta; Anderson, Richard A.; de Azambuja, Evandro; Poorvu, Philip D.; Kim, Hee Jeong; Villarreal-Garza, Cynthia; Pistilli, Barbara; Vaz-Luis, Ines; Saura, Cristina; et al.
Abstract : PURPOSE: Many patients and physicians remain concerned about the potential detrimental effects of pregnancy after breast cancer (BC) in terms of reproductive outcomes and maternal safety. This systematic review and meta-analysis aimed at providing updated evidence on these topics. METHODS: A systematic literature review was conducted to identify studies including patients with a pregnancy after BC (PROSPERO number CRD42020158324). Likelihood of pregnancy after BC, their reproductive outcomes, and maternal safety were assessed. Pooled relative risks, odds ratios (ORs), and hazard ratios (HRs) with 95% CIs were calculated using random effects models. RESULTS: Of 6, 462 identified records, 39 were included involving 8, 093, 401 women from the general population and 112, 840 patients with BC of whom 7, 505 had a pregnancy after diagnosis. BC survivors were significantly less likely to have a subsequent pregnancy compared with the general population (relative risk, 0.40; 95% CI, 0.32 to 0.49). Risks of caesarean section (OR, 1.14; 95% CI, 1.04 to 1.25), low birth weight (OR, 1.50; 95% CI, 1.31 to 1.73), preterm birth (OR, 1.45; 95% CI, 1.11 to 1.88), and small for gestational age (OR, 1.16; 95% CI, 1.01 to 1.33) were significantly higher in BC survivors, particularly in those with previous chemotherapy exposure, compared with the general population. No significantly increased risk of congenital abnormalities or other reproductive complications were observed. Compared to patients with BC without subsequent pregnancy, those with a pregnancy had better disease-free survival (HR, 0.66; 95% CI, 0.49 to 0.89) and overall survival (HR, 0.56; 95% CI, 0.45 to 0.68). Similar results were observed after correcting for potential confounders and irrespective of patient, tumor, and treatment characteristics, pregnancy outcome, and timing of pregnancy. CONCLUSION: These results provide reassuring evidence on the safety of conceiving in BC survivors. Patients' pregnancy desire should be considered a crucial component of their survivorship care plan.